(3CNHGQ GdReGf hef CHGOg GdMOKGf ef GdCee GdeGVjI hGdCLjGd GdNGdjI hGdeeGdjc GdOGKQIs - (3Ydj Hf GdMSjf Hf Ydj, CHh GdMSf GdeSYhOj,J (B346 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GHh GdMSfGdeSYhOjGeG HYO aGf Gddg Ld LdGdg hJbOSJ GSeGDg Ndb Ndbg ef ZjQ VQhQI s
(3BNQgG (B:s
(3ai cJGHg GdcQje GdPi GfRdg Ydi QShdg eMeO Ydjg GdSdGe Je hced GdcJGH s
(3PcQ ajg gjFI GdCQV heOfgG hLHGdgG hCfgGQgG heYGOfgG eUhQI Yf fSNI GdecJHI GdCgdjI HHGQjSs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B80s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B144 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B7 s
Keywords: (3GdJGQjNs